Novel method of quantitative assessment and stair-step surgical correction of a patient with congenital muscular torticollis - Rahul Varman; Ziyang Li; Joshua Demke (Otolaryngology Case Reports, 2022)
Background: Congenital muscular torticollis is a condition typically managed by a combination of nonsurgical and surgical means. Methods of preoperative evaluation and surgical treatment options remain areas of continued study. Methods: Novel MRI-based 3D visualization software is utilized to evaluate the sternocleidomastoid bilaterally for preoperative planning and stair-step surgical treatment of an eight-year-old male with congenital muscular torticollis. Results: Presurgical measurements demonstrated head tilt of 8°, with spine radiographs revealing leftward listhesis of cervical spine, with Cobb angle 23°. Utilizing a 3DSlicer 4.10, total SCM discordance was measured to be 2cm. A 3cm stair-step plasty was performed. At 9 month follow up, head tilt was noted to be normalized on postoperative frontal imaging. Conclusion: 3D visualization techniques can improve preoperative evaluation and patient education. Continued reports and studies regarding evaluation and treatment of muscular torticollis surgical candidates can help delineate factors and techniques for improved patient outcomes.